2016
DOI: 10.17261/pressacademia.2016116527
|View full text |Cite
|
Sign up to set email alerts
|

A confirmatory factor analysis of the source model for celebrity endorsement

Abstract: Marketing managers nowadays use one of the most common advertising strategies to grab persons' time in order to inform the remarkable features of their products: they use celebrities to endorse their products. Several researchers have studied the model of celebrity endorsement. One of the most important is source model, which covers source credibility model and source attractiveness model. This paper evaluated the source model of celebrity endorsement developed by Ohanian (1990) and make a generalization using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
1
2
0
Order By: Relevance
“…This study found that of the three personal characteristics of SMI, only SMI's expertise and attractiveness influenced consumer attitudes towards the brand. The findings regarding the positive influence of SMI expertise on brand attitudes are in accordance with the research of Ulkhaq et al (2016) who found that SMI expertise had a greater impact on consumer purchase intentions than attractiveness and trustworthiness. Meanwhile, Tanjung and Hudrasyah (2019) stated that SMI's expertise significantly influences consumer attitudes towards the brands promoted by SMI and their buying interest.…”
Section: Effect Of Expertise On Attitude Toward the Brandsupporting
confidence: 89%
See 1 more Smart Citation
“…This study found that of the three personal characteristics of SMI, only SMI's expertise and attractiveness influenced consumer attitudes towards the brand. The findings regarding the positive influence of SMI expertise on brand attitudes are in accordance with the research of Ulkhaq et al (2016) who found that SMI expertise had a greater impact on consumer purchase intentions than attractiveness and trustworthiness. Meanwhile, Tanjung and Hudrasyah (2019) stated that SMI's expertise significantly influences consumer attitudes towards the brands promoted by SMI and their buying interest.…”
Section: Effect Of Expertise On Attitude Toward the Brandsupporting
confidence: 89%
“…When consumers feel that an SMI has expertise in the brand, they tend to be more likely to trust the advertisements delivered by the SMI (Mansour & Diab, 2016). Ulkhaq et al (2016) found that SMI expertise has a greater impact on consumer purchase intentions than attractiveness and trustworthiness. An SMI who has knowledge and expertise on the product he recommends will be more effective in persuading consumers to buy the brand through his positive attitude towards the brand (Aw & Labrecque, 2020).…”
Section: Introductionmentioning
confidence: 98%
“…It means the ability of celebrities to provide knowledge to others based on their background, education, skills or efficiency, this constitutes a person's qualifications (Horai et al, 1974). The semantic expertise scales includes expert, experienced, knowledgeable, qualified and skilled (Ulkhaq et al, 2016). The expert celebrity consider more persuasive and can have an effect on the decision to purchase goods than non-experts, Ohanian argued that attractiveness and trustworthiness have less effect on customer purchasing intentions than celebrity endorsers ' expertise.…”
Section: Celebrity Expertisementioning
confidence: 99%